Source Base Importance in Methodologies of Historic-Pedagogical Study - Valentyna Shpak (Pedagogical Discourse, 2013)
The author is illuminated source bases importance in methodologies of historic-pedagogical study. The scientific knowledge structure is revealed, the necessity of its studying by means of source-conduct analysis and syntheses methods is argued. The stages of analytical critics and synthesized shouts in work with historic-pedagogical sources are characterized. Scipping the requirements to source interpretation base in methodologies of historic-pedagogical studies proclaims negatively as to the logic and contents of a dissertation work, leads to inexactness in procedure of history searching and interpretation of studies’ results.